EVALUASI PELATIHAN PEMBUATAN KONTEN VISUAL UNTUK SOSIAL MEDIA MENGGUNAKAN MODEL KIRKPATRICK DI BBPVP SERANG - Devi Kurniati; Dyah Permatasari; Reggy Putra Pratama Widika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of evaluating the effectiveness of visual content creation training for social media in improving participants’ competencies at BBPVP Serang. Evaluation is necessary to determine the extent to which the training provides benefits in increasing knowledge, skills, behavioral changes, and outcomes achieved by participants after attending the training. This study aims to evaluate the implementation of visual content creation training for social media based on the four levels of the Kirkpatrick evaluation model, namely reaction, learning, behavior, and results. This research employed a qualitative approach with an evaluative method. Data collection techniques were conducted through interviews, observations, and documentation involving training participants, instructors, and training organizers as data sources. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that participants gave positive responses to the training implementation, experienced improvements in knowledge and skills in creating visual content, demonstrated behavioral changes in applying skills during practical work activities, and gained positive impacts on competency improvement and work readiness. Thus, the visual content creation training for social media at BBPVP Serang is considered effective based on the Kirkpatrick evaluation model.